Konstruksi Sosial atas Kesempatan Kerja: Studi Kasus Peran Dinas Tenaga Kerja di Kabupaten Asahan: Social Construction of Employment Opportunities: A Case Study of the Role of the Manpower Office in Asahan Regency - Wijaya, Putra; Irmayani, Tengku; Bengkel, Bengkel (Universitas Negeri Medan, 2025)
The unemployment rate in Asahan Regency, North Sumatra, remains above the national average despite a numerical downward trend. This study analyzes the role of the Asahan Regency Manpower Office in expanding employment opportunities, focusing on the social construction of labor policy. Data were collected through in-depth interviews, participatory observations, and a review of policy documents and BPS statistics. The findings reveal that although the Manpower Office has implemented job placement programs, competency training, and the Employment Information System (SIKAS), its effectiveness is hindered by three main factors: (1) a mismatch between training programs and industry needs, (2) limited dissemination of the SIKAS digital platform (only 30% of the workforce is aware of it), and (3) budget constraints (Rp120–150 million per year) and limited human resources (only 30% of employees meet functional criteria). Key findings indicate that while 86.4% of training participants (2022) obtained certification, only 49.7% were absorbed into the labor market, with the majority being unemployed individuals with high school (28.3%) and elementary school (31.5%) education. This disparity reflects a failure in bridging the skills mismatch. Meanwhile, job placements increased from 410 (2020) to 963 (2022), but this growth was reactive to global market demands rather than the result of systematic planning. In terms of communication, minimal collaboration with local media has led to information gaps, preventing outreach to vulnerable groups. This study recommends a policy reorientation by aligning training curricula with industry demands, intensifying SIKAS dissemination through community collaboration, and strengthening the institutional capacity.